Implementasi Metode Fuzzy Mamdani Untuk Menentukan Tingkat Jumlah Pernikahan Dini Tahun 2022 Kabupaten Barru - Baso Riadi Husda; Muh. Nakkir; Ahmad Albar; Andi Muhammad Asfiandy; Muh.Faiz Fakhrizal; Muhammad Ahsin Thahir (PT. Global Research Collaboration, 2023)
Marriage is an important moment in the life of every individual that connects physically and emotionally between a man and a woman as husband and wife, with the aim of forming a balanced and lasting family based on belief in God Almighty. Early marriage is a marriage that takes place in their teens, who have not yet reached or have just passed their teenage years. According to the World Health Organization (WHO), the age range for adolescents is 12-24 years. In this research, we will implement the Mamdani fuzzy method to determine the level of the number of early marriages in 2022 in Barru district. In this research, we will implement the Mamdani fuzzy method to determine the level of the number of early marriages in 2022 in Barru district. In conclusion, by combining statistical data obtained with the implemented Fuzzy Mamdani method, we can determine the level of the number of early marriages in 2022 in Barru district based on the input variables provided.